The α7 Nicotinic Acetylcholine Receptor: A Promising Target for the Treatment of Fibrotic Skin Disorders - Stegemann, Agatha; Flis, Damian; Ziolkowski, Wieslaw; Distler, Jörg; Steinbrink, Kerstin; Böhm, Markus (Journal of Investigative Dermatology, 2020)
Targeting neuroendocrine receptors can be considered as another interesting approach to treating fibrotic disorders. Previously, we could demonstrate that tropisetron, a classical serotonin receptor blocker, can modulate collagen synthesis and acts in vitro through the α7 nicotinic acetylcholine receptor (α7nAchR). Here, we used a pharmacologic approach with specific α7nAchR agonists to validate this hypothesis. PHA-543613, an α7nAchR-specific agonist, not only prevented but also reversed established skin fibrosis of mice injected with bleomycin. Interestingly, agonistic stimulation of α7nAchR also attenuated experimental skin fibrosis in the non–inflammation driven adenovirus coding for TGFβ receptor Iact mouse model, indicating fibroblast-mediated and not only anti-inflammatory effects of such agents. The fibroblast-mediated effects were confirmed in vitro using human dermal fibroblasts, in which the α7nAchR-specific agonists strongly reduced the impact of TGFβ1-mediated expression on collagen and myofibroblast marker expression. These actions were linked to modulation of the redox-sensitive transcription factor JunB and impairment of the mitochondrial respiratory system. Our results indicate that pharmacologic stimulation of the α7nAchR could be a promising target for treatment of patients with skin fibrotic diseases. Moreover, our results suggest a mechanistic axis of collagen synthesis regulation through the mitochondrial respiratory system.
CRIS-Team Scopus Importer:2020-06-02